2019
DOI: 10.1002/jcb.28938
|View full text |Cite
|
Sign up to set email alerts
|

Screening candidate microRNA‐mRNA network for predicting the response to chemoresistance in osteosarcoma by bioinformatics analysis

Abstract: The search for biomarkers is important for providing more targeted treatments for osteosarcoma patients with chemoresistance. In this study, differentially expressed microRNAs (miRNAs) were identified from miRNA expression profiles. And the target messenger RNAs (mRNAs) of miRNA were obtained from two websites in public domains. Analysis of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway by these miRNA targets suggests that they may have potential links to osteosarcoma chemoresist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Similarly, they also identified 15 differentially expressed miRNAs (DEMs) in GSE39040, and functional enrichment analysis showed that upregulated DEMs were mainly enriched in cell growth and response to growth factor, and downregulated DEMs were involved in cytokine receptor activity. Moreover, using GEO database, Dai et al (21) screened candidate genes for predicting the response to chemoresistance in osteosarcoma by miRNA-mRNA network. However, the differentially selected genes in these studies are all based on a single dataset, and the small size of samples will cause the instability of results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, they also identified 15 differentially expressed miRNAs (DEMs) in GSE39040, and functional enrichment analysis showed that upregulated DEMs were mainly enriched in cell growth and response to growth factor, and downregulated DEMs were involved in cytokine receptor activity. Moreover, using GEO database, Dai et al (21) screened candidate genes for predicting the response to chemoresistance in osteosarcoma by miRNA-mRNA network. However, the differentially selected genes in these studies are all based on a single dataset, and the small size of samples will cause the instability of results.…”
Section: Discussionmentioning
confidence: 99%
“…Pertinent references were searched, and two related published risk models were selected including an eight-gene (PMID: 31333788) [45], a four-gene (PMID: 31146489) [59], a ten-gene (PMID: 31090103) [60], and a nineteengene (PMID: 30604867) [61] signature risk model. To make the models comparable, a multi-factor Cox regression was run and the RiskScore of the training set samples was recalculated according to the corresponding genes in the model of the present study.…”
Section: Comparative Study Of Other Risk Modelsmentioning
confidence: 99%
“…Recent high-throughput studies are contributing to an improved understanding of the molecular mechanism concerning various phenotypes, such as carcinogenesis (Sun et al 2018 ), metastasis (Tian et al 2017 ), and chemoresistance (Dai et al 2019 ). These cancer-associated phenotypes are at least partly controlled by differentially expressed genes (DEGs), including long non-coding RNA (lncRNA), microRNA (miRNA), and protein-coding gene (PCG).…”
Section: Introductionmentioning
confidence: 99%